Management and treatment of men affected by metastatic prostate cancer: evidence‐based recommendations for practice. Issue 1 (3rd September 2015) - Paterson, Catherine; Alashkham, Abduelmenem; Windsor, Phyllis; Nabi, Ghulam
ABSTRACT: Currently, 250 000 men are affected by prostate cancer in the UK. Clinical guidance is crucial for nurses involved in the care delivery for men with advanced prostate cancer and for their families to maximize their quality and quantity of life. It is essential that nurses understand how prostate cancer is diagnosed, can recognize signs of disease progression, are familiar with disease management, and can educate patients and manage any symptoms appropriately and effectively. Therefore, the aim of this paper is to review current evidence‐based guidelines in relation to care delivery for men with metastatic prostate cancer in order to optimize best supportive care. A literature review was conducted in a range of electronic databases (DARE, Cochrane, MEDLINE, BNI, PsychINFO, EMBASE and CIHAHL) to identify studies employing qualitative and/or quantitative methods. National (UK) and European clinical guidelines were also reviewed. Methodological evaluation was conducted and the evidence‐based recommendations were integrated in a narrative synthesis. Supportive care is a person‐centred approach to the provision of the necessary services for those living with or affected by cancer to meet their informational, spiritual, emotional, social or physical needs during diagnosis, treatment or follow‐up phases including issues of health promotion, survivorship, palliation and bereavement. A multidisciplinary and proactive approach to the management of men with metastatic prostate cancer ensures safe and effective supportive care delivery. Nurses involved in the care delivery for this patient group need to be aware of the complex physical and psychological supportive care needs, and evidence‐based management care plans to ensure a personalized and tailored support to optimize quality of life.